Aflatoxin B1 Degradation and Detoxification by Escherichia coli CG1061 Isolated From Chicken Cecum - Wang, Lingling; Wu, Jun; Liu, Zhiwen; Shi, Yutao; Liu, Jinqiu; Xu, Xiaofan; Hao, Shuxian; Mu, Peiqiang; Deng, Fengru; Deng, Yiqun (Frontiers in Pharmacology, 2019)
Aflatoxin B1 (AFB1) is one of the most hazardous mycotoxins contamination in 19 food and feed products, which leads to hepatocellular carcinoma in humans and 20 animals. In the present study, we isolated and characterized an AFB1 degrading 21 bacteria CG1061 from chicken cecum, exhibited an 93.7% AFB1 degradation rate by 22 HPLC. 16S rRNA gene sequence analysis and a multiplex PCR experiment 23 demonstrated that CG1061 was a non-pathogenic Escherichia coli. The culture 24 supernatant of E. coli CG1061 showed an 61.8% degradation rate, whereas the 25 degradation rates produced by the intracellular extracts was only 17.6%, indicating 26 that the active component was constitutively secreted into the extracellular space. The 27 degradation rate decreased from 61.8% to 37.5% when the culture supernatant was 28 treated with 1 mg/mL proteinase K, and remained 51.3% when that treated with 29 100 ℃ for 20 min. We postulated that AFB1 degradation was mediated by 30 heat-resistant proteins. The content of AFB1 decreased rapidly when it was incubated 31 with the culture supernatant during the first 24 h. The optimal incubation pH and 32 temperature were pH 8.5 and 55 ℃ respectively. According to the UPLC Q-TOF MS 33 analysis, AFB1 was bio-transformed to the product C16H14O5 and other metabolites. 34 Based on the results of in vitro experiments on chicken hepatocellular carcinoma 35 (LMH) cells and in vivo experiments on mice, we confirmed that CG1061-degraded 36 AFB1 are less toxic than the standard AFB1. E. coli CG1061 isolated from healthy 37 chicken cerum is more likely to colonize the animal gut, which might be an excellent 38 candidate for the detoxification of AFB1 in food and feed industry